2022
DOI: 10.1017/s0960258522000204
|View full text |Cite
|
Sign up to set email alerts
|

Characterization and diversity of seed endophytic bacteria of the endemic holoparasitic plant Cistanche armena (Orobanchaceae) from a semi-desert area in Armenia

Abstract: We explored the seed-associated bacterial endophytic microbiome in seeds of the endemic holoparasitic species Cistanche armena from a saline and arid habitat in Armenia. A combination of culture-dependent and molecular techniques was employed for identifying the seed endomicrobiome (culturable and unculturable). From surface-sterilized seeds, 10 phyla, comprising 256 endophytic bacterial genera, were identified. Of the culturable strains, we also investigated the plant growth-promoting (PGP) traits. Most of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
22
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 8 publications
(23 citation statements)
references
References 63 publications
1
22
0
Order By: Relevance
“…3 A, B). Recent studies have reported the enrichment of potentially beneficial endophytic bacteria, such as Paenibacillus and Bacillus [ 70 , 71 ], in some plant seeds. These microbes may preferentially colonize seeds, thus, providing a barrier against pathogens.…”
Section: Discussionmentioning
confidence: 99%
“…3 A, B). Recent studies have reported the enrichment of potentially beneficial endophytic bacteria, such as Paenibacillus and Bacillus [ 70 , 71 ], in some plant seeds. These microbes may preferentially colonize seeds, thus, providing a barrier against pathogens.…”
Section: Discussionmentioning
confidence: 99%
“…These microorganisms can have the potential to mitigate the impacts of unfavourable environmental conditions, as well as the negative effects of plant pathogen infections 19 , 35 , 36 . Due to the dynamic and brief development of species from the Orobanchaceae family, microorganisms can respond to and potentially aid the current needs of these heterotrophic plants; for example, microorganisms in the sunflower rhizosphere affect parasitic seed germination and growth 46 as well as endophytic bacteria in seeds of Cistanche armena are able to improve the tolerance of parasitic plants under stress conditions in their natural habitat 37 . On the other hand, for the few parasitic plants that are dangerous weeds of economic importance, microbial communities may play an important role in mitigating the negative effects of infections caused by these plants.…”
Section: Discussionmentioning
confidence: 99%
“…Orobancheae species are poorly known in terms of the bacterial and fungal microbiota that inhabit them [32][33][34][35][36][37][38] . These microorganisms can have the potential to mitigate the impacts of unfavourable environmental conditions, as well as the negative effects of plant pathogen infections 19,35,36 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…3A, B). Recent studies have reported the enrichment of potentially bene cial endophytic bacteria, such as Paenibacillus and Bacillus [71,72], in some plant seeds. These microbes may preferentially colonize seeds, thus, providing a barrier against pathogens.…”
Section: Association Of Speci C Bacteria In the Resistant Cotton Geno...mentioning
confidence: 99%